Pengaruh Literasi Perpajakan Dan Persepsi Sanksi Pajak Terhadap Minat Pelaporan Pajak Pada Generasi Z - Devi, Larasati; Wulur, Yolanda; Salbila, Tiara; Pratiwi, Natasya; Linawati, Linawati (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of tax literacy and perceptions of tax sanctions on tax reporting intention among Generation Z students. The study employs a quantitative approach using a survey method involving 100 Generation Z student respondents in South Jakarta, selected through purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS version 27. The results indicate that tax literacy and perceptions of tax sanctions each have a positive and significant effect on tax reporting intention. These findings contribute to strengthening the literature on the formation of tax compliance intentions among younger generations and provide practical implications for higher education institutions and tax authorities to enhance tax education and sanction socialization in order to foster a culture of tax awareness from an early age.